The Medical Management of Gastroesophageal Reflux Disease: A Narrative Review - Paul T. Kröner; Pedro Cortés; Frank J. Lukens (SAGE Publishing, 2021)
Objective The medical management of gastroesophageal reflux disease (GERD) continues to evolve. Our aim was to systematically assess the literature to provide an updated review of the evidence on lifestyle modifications and pharmacological therapy for the management of GERD. Background The cornerstones of GERD medical management consist of lifestyle modifications and pharmacologic agents. Most recently, evidence has emerged linking anti-reflux pharmacologic therapy to adverse events, such as kidney injury, metabolic bone disease, myocardial infarction, and even dementia, among others. Methods A systematic search of the databases of PubMed/MEDLINE, Embase, and Cochrane Library was performed for articles on the medical management of GERD between inception and March 1, 2021. Conclusion Although pharmacological therapy has been associated with potential adverse events, further research is needed to determine if this association exists. For this reason, lifestyle modifications should be considered first-line, while pharmacologic therapy can be considered in patients in whom lifestyle modifications have proven to be ineffective in controlling their symptoms or cannot institute them. Naturally, extra-esophageal causes for GERD-like symptoms must be considered on suspected high-risk patients and excluded before considering treatment for GERD.